1993
DOI: 10.1111/j.1471-6402.1993.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnocultural Comparisons in Styles of Love

Abstract: Ethnocultural background and gender were investigated as correlates of love styles in an ethnically diverse sample of university students in Toronto. Women viewed love as more friendship oriented, more pragmatic, but less permissive than did men, findings consistent with previous research with American college students. Ethnocultural differences or Gender x Ethnocultural Background interactions were also found. In line with an expected contrast between Asian and Western cultural traditions regarding love, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 12 publications
0
23
0
3
Order By: Relevance
“…Gender differences and their associations with Lee's love styles have been studied extensively. Some research reported no gender differences with regards to Agape (Dion & Dion, 1993;Montgomery & Sorell, 1997). A number of studies reported that women favored the style of Agape more than men (e.g., Davies, 2001;Schultz et al, 2001).…”
Section: Marriage and Family Reviewmentioning
confidence: 95%
“…Gender differences and their associations with Lee's love styles have been studied extensively. Some research reported no gender differences with regards to Agape (Dion & Dion, 1993;Montgomery & Sorell, 1997). A number of studies reported that women favored the style of Agape more than men (e.g., Davies, 2001;Schultz et al, 2001).…”
Section: Marriage and Family Reviewmentioning
confidence: 95%
“…In the Hong Kong Chinese culture with more marriageage men than women, according to sex ratios theory (Pedersen, 1991), dating individuals prefer long-term, monogamous dating relationships and have stronger commitment to dating relationships (Schmitt, 2005). Furthermore, given the cultural norms of interdependence (Markus, & Kitayama, 1991), Chinese dating individuals were expected to preserve harmonious relationships with the partner and his/her family members (Dion, & Dion, 1993). Thus, Chinese with high attachment avoidance, who violate the norm of interdependence (Friedman et al, 2010), may experience more relational conflict and in turn invite more psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Sex (Dion & Dion, 1993;Fehr & Broughton, 2001), age (Neto, 2001;Yancey & Eastman, 1995) and level of education (Hoelter, Axinn, & Ghimire, 2004) play a role in determining how love is viewed, expressed and experienced within marriage. Relationship factors such as time together with the partner (Grote & Friez, 1998), total number of children (Montgomery & Sorell, 1997), may also influence marital satisfaction and the well-being of the person.…”
Section: Introductionmentioning
confidence: 99%